The Use of Passive and Invasive CO2 Elimination via interventional Lung Assist System iLA [Novalung®] on a Small Intensive Care Unit of a Hospital for Basic and Regular Care. Issue 1 (18th June 2019) - V, Kostov; M, Maier, Stoerzbach S; T, Barth; R, Clement, Döffert J; M, Oberhoff; T, Anger
No abstract available